Analisis Faktor Penghambat Masyarakat Dalam Pendaftaran Tanah - Resty Annisa Kusnadi; Mohtana Kharisma Kadri; Rahmat Aris Pratomo; Arief Hidayat (COMPACT: Spatial Development Journal, 2023)
In order to guarantee legal certainty regarding land ownership and control, the government is conducting land registration throughout Indonesia. Based on data quoted from the 2022 Integration DAK Document, it is stated that Kampung Pasole Banar has land problems, namely the lack of ownership of land title certificates. The formulation of the problem in this study is what are the inhibiting factors of the community in registering land in the RT. 17 Village of Pasole Banar, Sidodamai Village from the public's perception. The type of research used in this research is quantitative research with exploratory factor analysis methods. The results of the study show that the community's inhibiting factors in land registration at RT. 17 Kampung Pasole Banar Sidodamai Village is divided into two, namely the inhibiting factors from the community and the inhibiting factors from the government.